Emperor and Law in The Orations of Julian „The Apostate“ - Šarkić, Srđan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Julian „the Apostate“ was Roman Emperor from 361 to 363 and a noted philosopher and Greek writer. A member of the Constantinian dynasty (his father Julius Constantius, was Constantine’s brother), Julian was a man of unusually complex character: he was the military commander, the theosophist, the social reformer and the man of letter. He was the last non-Christian ruler of the Roman Empire and it was his desire to bring the Empire back to its ancient Roman values in order to save it from dissolution. He purged the top-heavy state bureaucracy and attempted to revive traditional Roman religious practices at the cost of Christianity. His rejection of Christianity in favour of Neoplatonic paganism caused him to be called Julian the Apostate (Greek ’Аποστάτης or Пαραβάτης = „Transgressor“) by the Church. He was the last Emperor of the Constantinian dynasty, the Empire’s first Christian dynasty.            The substitution of the Roman Republic by Hellenistic oriental monarchy, the process extending through three centuries, found its legal-theoretical justification in the Hellenistic theory of a monarch as a live or spiritualized law (νόμος εμψυχος, lex animata). This theory is in contrary to the Roman republican concept of Emperor (princeps, dominus) as a mandatary of Roman people, especially expressed by Emperor Julian in his orations.
Keywords: Philosophy; Law; Emperor; Libanios; Themistios; Constantius; Julian